The Role of the Organization of Islamic Cooperation (OIC) Through OIC-2025: Programme of Action in Achieving Sustainable Development Goals in 2018-2019 - Suhafid, Muh. Zulhamdi (International Journal of Global Sustainable Research, 2024)
The Sustainable Development Goals (SDGs) represent a global agenda aimed at promoting human development, considering the declining quality of life worldwide. This has prompted all Muslim countries to collaborate in creating a fair, prosperous, and prosperous life. This article utilizes the basic concept of SDGs combined with the theory of international organizations. The research method used in this article is qualitative-descriptive through Secondary Data Analysis (SDA). Therefore, this article will discuss more broadly the role of the Organization of Islamic Cooperation (OIC) in realizing SDGs action programs. The author's analysis in this article shows that OIC has long been implementing programs oriented towards and supporting SDGs. This can be seen in OIC's program, the OIC-2025: Programme of Action in 2018-2019. This program is a manifestation of Islamic countries' efforts to create and address all humanitarian issues. There are 13 priority areas of OIC that direct its programs towards the 4 pillars of SDGs development.